FORMATION OF NUTRITIONAL BEHAVIOR OF ENGINEERING AND TECHNICAL WORKERS OF COAL ENTERPRISES - Тапешкина, Наталья Васильевна; Алексеева, Наталья Сергеевна; Блажина, Ольга Николаевна; Ямщикова, Анастасия Валерьевна; Корсакова, Татьяна Георгиевна (Medicine in Kuzbass, 2024)
Introduction. Nutrition is one of the important environmental factors that determine human health. Improper nutritional behavior is the leading cause of poor health and the development of diet-dependent diseases. The purpose of this research was to study the features of the formation of nutritional behavior of engineering and technical workers, who organize and manage the production process of coal enterprises in the South of Kuzbass at the current stage. Material and methods. A questionnaire was conducted to assess the nutritional behavior, and the study was selective. The total sample was 54 persons (men). When studying nutritional behavior, it was taken into account: nutrition awareness, food choice, dietary regime. The calculation of the index of the weight index was carried out when ranking the factors of awareness in matters of nutrition. Results. The determining factors in the choice of food products among the engineering and technical workers were taste preferences (40.0 %) and the cost of a food product (33.0 %). The nutritional value of a food product was taken into account when purchasing only 4.0 % of the respondents. Analysis of the frequency of food consumption showed that daily bread and bakery products, potatoes, butter and vegetable oils were present in the diet and only 85-92 % of the engineering and technical workers consumed meat, vegetables, pasta, and groats daily. Biologically valuable foods (fish, eggs and dairy products) were present in daily diets in 23 %, 16 % and 41 % of the cases, respectively. Although nutritional behavior was influenced by the level of education, there were 1.8 times more people who were informed about nutrition among the engineering and technical workers with higher education (76.3 %) than among people with secondary specialized vocational education (42.6 %), a significant role in the choice of food in families (weight index – 18.6) was assigned to taste preferences in the family. Conclusion. The elaboration of measures of a sanitary and educational nature among engineering and technical workers on the issues of healthy nutrition should be carried out taking into account the previously identified violations, be individual and regional in nature.